Filogeni Timun Laut (Holothuroidea: Stichopodidae) Berdasarkan Karakteristik Morfologis - Ismiliana Wirawati; Pradina Purwati (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Phylogeny of Sea Cucumbers (Holothuroidea: Stichopodidae) Based on Morphological Characteristics. Identifiers in the class of sea cucumber (Holothuroidea, Echinodermata) constitute the external morphology, internal organs, and spicules. These characteristics may indicate a high level of similarity for particular families, including family Stichopodidae. This family is one of the Holothuroidea (Echinodermata) that represents the majority of commercial species found widespread in the tropical shallow waters. Until now, the evolution of sea cucumber based on morphological characteristics used to determine the status of the characteristics applicable to the phylogeny analysis is still under debate. In fact, research on the phylogeny of Stichopodidae, has not been done yet. This paper reports the phylogeny study of Stichopodidae species in Indonesia to determine the closeness among its species. Specimens used in this study were the collection of Research Center for Oceanography LIPI consisting of nine species of Stichopodidae (as ingroup) and two species of Holothuriidae (as outgroup). The construction of phylogeny tree was done by applying the maximum parsimony method and PAUP 4.0b program using 78 morphological characteristics. It resulted in two phylogeny trees separating consistently the genus Stichopus from the genus Thelenota (bootstrap 99% and 100%) with the stable position in each genus. Both these genera of Stichopodidae have the same number of synapomorphs. Stichopus has ten homoplastic characteristics among its species, while Thelenota does not have any. Six of the nine species of Stichopodidae show autapomorph characteristics which are proper to species level